PERILAKU KONSUMEN DALAM PEMBELIAN BERAS SIGER DI KELOMPOK WANITA TANI MELATI PEKON MARGOSARI KECAMATAN PAGELARAN UTARA - Novia Setyaningrum; Bustanul Arifin; Zainal Abidin (Lampung University, 2020)
This study aims at analyzing consumers attitudes towards attributes of Siger Rice, consumer decisionmaking processes in the purchase of Siger Rice and dominant factors that influence the decision inpurchasing Siger Rice. Data collection was conducted from January to April 2019. The sampling techniqueused in the study was snowballing sampling. The number of samples in this study were 38 housewives whomet the criteria of buying and consuming Siger Rice. The first objective was analyzed by the FishbeinMultiattribute Model, the second objective was analyzed by qualitative descriptive analysis, and the third objective was analyzed by analysis of the main components. The results showed that the taste attribute gotthe highest attitude score of 18.96, while the ease of obtaining attribute had the lowest attitude score of11.87. The process of making Siger Rice purchase decisions by consumers were through all stages, the need recognition, information searching, evaluation of alternatives, purchase decisions and post-purchaseevaluation. There are three dominant components that influence the purchasing decision of Siger rice, i.ethe price conformity, attractiveness, and habit.Key words: analysis of main components, consumer attitudes, consumer behavior, siger rice.